LOGISTICS AND SUPPLY CHAIN APPROACH TO SERVITIZATION - Shivendra, Mishra (2013)
Service quality is very important factor to study in order to understand the correct approach of logistics and supply chain in order to offer servitization. It is equally important for organizations as well as researchers to understand how to evaluate the consumer’s perspective and translate them into actual service delivery in order to attain maximum customer satisfaction. The primary purpose of servitization is to attain maximum customer satisfaction. The main purpose of this particular research is to study the SERVQUAL model in context to automobile industry and evaluate the perception and expectation of service in context to servitized products. Self-compiled questionnaire from SERVQUAL instrument was created into two types. One was used to collect the opinion from consumers of a particular case company and to understand their perspective of service quality offered. The other was used to collect the opinion of the employees from the same company in order to understand their view on quality of its servitized offering.From the analysis carried out through SERVQUAL model it was found that service quality of servitized products is at moderate level. The data collected showed the gap between perceived and expected level of service quality in context to automobile industry. The findings of this dissertation suggest that the logistics and supply chain approach of the servitization in automotive sector is pretty good in Indian subcontinent but it needs development in some of the key areas. This dissertation contributes in further development of service quality concept in servitized environment and its result and implications can be used as guiding tool for management and adaptation of servitization in automobile industry.